2013
DOI: 10.1128/jvi.00854-12
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor A Promotes Vaccinia Virus Entry into Host Cells via Activation of the Akt Pathway

Abstract: Vaccinia virus (VV) is an enveloped DNA virus from the poxvirus family and has played a crucial role in the eradication of smallpox. It continues to be used in immunotherapy for the prevention of infectious diseases and treatment of cancer. However, the mechanisms of poxvirus entry, the host factors that affect viral virulence, and the reasons for its natural tropism for tumor cells are incompletely understood. By studying the effect of hypoxia on VV infection, we found that vascular endothelial growth factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…PIKfyve facilitates Rab7a‐independent fusion of LEs with each other and with LYs 30. In addition, the PIKfyve‐activating kinase, Akt, previously implicated in VACV entry 70, 71, was a hit in our screen. Interestingly, Akt has been reported to phosphorylate PIKfyve to facilitate lysosomal trafficking and degradation of EGFR 72.…”
Section: Discussionmentioning
confidence: 93%
“…PIKfyve facilitates Rab7a‐independent fusion of LEs with each other and with LYs 30. In addition, the PIKfyve‐activating kinase, Akt, previously implicated in VACV entry 70, 71, was a hit in our screen. Interestingly, Akt has been reported to phosphorylate PIKfyve to facilitate lysosomal trafficking and degradation of EGFR 72.…”
Section: Discussionmentioning
confidence: 93%
“…Another gene found in tumor cells that can influence OV therapy is VEGF. Our group has demonstrated that VEGF-A increases VV internalization and in turn replication levels ( 135 ). Therefore, oncolytic VV can take advantage of the increased expression of VEGF by tumor cells to increase delivery of therapeutic genes which in turn increases the efficacy and potency of the treatment.…”
Section: Tumor Cell Biology and Viral Therapymentioning
confidence: 99%
“…CCL chemokines (CCL2, CCL3, CCL4, CCL5, and CCL11) were found in acute ZIKV infection. The role of CCL5 in the arbovirus-induced immunopathology remains a controversial issue, but this chemokine along with CCL2 and CCL3 were previously linked to severity of dengue and Japanese encephalitis virus infections, including neurological diseases and impairment of neuronal survival [23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%